Tenascin C in radiation‐induced lung damage: Pathological expression and serum level elevation. Issue 20 (1st September 2022) - Toyomasu, Yutaka; Matsui, Kenta; Omori, Kazuki; Takada, Akinori; Imanaka‐Yoshida, Kyoko; Tawara, Isao; Shimamoto, Akira; Takao, Motoshi; Kobayashi, Hiroyasu; Tomaru, Atsushi; Fujimoto, Hajime; Kobayashi, Tetsu; et al.
Abstract: Radiation‐induced lung damage (RILD) is a critical problem in lung cancer radiotherapy, and it is difficult to predict its severity. Although no biomarkers for RILD have been established, tenascin C (TNC) is an extracellular matrix glycoprotein involved in the remodeling of damaged tissues and has been implicated in inflammation and fibrosis. We report the unique case of a 36‐year‐old man with adenocarcinoma of the lung, Union for International Cancer Control stage IIIB, who was treated with radiotherapy before lung surgery. The surgical specimen showed histopathological expression of TNC in the region where radiation pneumonitis was observed radiographically. Serum TNC levels were elevated after radiotherapy. In this case, TNC is suggested to be implicated in RILD and may be a potential candidate as a biomarker for the onset and severity of the condition. Abstract : We report a case of lung cancer, which was treated with radiotherapy before surgery. The surgical specimen showed histopathological expression of tenascin C (TNC) in the region where radiation pneumonitis was observed radiographically. In addition, serum TNC levels were elevated after radiotherapy. TNC may be a potential biomarker for radiation pneumonitis.